Cholesterol Granuloma in Odontogenic Cyst: An Enigmatic Lesion. (13th December 2016) - Kamboj, Mala; Devi, Anju; Gupta, Shruti
Abstract : Cholesterol granuloma (CG) is the outcome of the foreign body type of response to the accumulation of cholesterol crystals and is frequently present in conjunction with chronic middle ear diseases. Recently, cases of CG in jaws have been reported, but still, very few cases have been found of CG in dental literature. This article presents three rare cases of CG in the wall of odontogenic cysts emphasizing on its possible role in expansion of the associated lesion and bone erosion. It also lays stress on the fact that more cases of CG should be reported so that its nature and pathogenesis in the oral cavity become more perceivable.